Gene Targeting Protocols - Kmiec, Eric B.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2000)
In Gene Targeting Protocols, a panel of innovative investigators present in readily reproducible detail the latest techniques for gene replacement, gene knockout, and gene repair in both animals and plants. These expert researchers review the best gene transfer vehicles (liposomes, PEI, and EPD), discuss the parameters that affect vector uptake, and detail successful methods for gene targeting (Cre-ox, and adeno and adeno-associated viruses). The methods include two fundamentally different approaches to gene targeting- one using a fusion protein to deliver a vector to a virus for possible therapeutic effect, and one entailing an episomal-based Epstein-Barr vector that can modulate the chromatin assembly process, and thus overcome a serious barrier to therapeutic gene targeting. The book also has several techniques for using oligonucleotides in gene targeting, a methodology that may revolutionize the entire field. Innovative and wide ranging, Gene Targeting Protocols offers today's researchers robust and proven gene-targeting techniques that are essential to understanding and regulating biological processes at the genetic level.
Nucleic Acid Transfer Using Cationic Lipids -- Optimizing Polyethylenimine-Based Gene Transfer into Mammalian Brain for Analysis of Promoter Regulation and Protein Function -- Gene Transfer and Drug Delivery by Electronic Pulse Delivery -- Strategies for Improving the Frequency and Assessment of Homologous Recombination -- Effective Gene Transfer Using Viral Vectors Based on SV40 -- Rapid Generation of Isogenic Mammalian Cell Lines Expressing Recombinant Transgenes by Use of Cre Recombinase -- Site-Directed Alteration of Genomic DNA by Small-Fragment Homologous Replacement -- Mutation Correction by Homologous Recombination with an Adenovirus Vector -- Site-Specific Targeting of DNA Plasmids to Chromosome 19 Using AAV Cis and Trans Sequences -- Adeno-Associated Virus Based Gene Therapy in Skeletal Muscle -- Rapid Establishment of Myeloma Cell Lines Expressing Fab(Tac)-Protamine, a Targetable Protein Vector, Directed Against High-Affinity ?-Chain of Human Interleukin-2 Receptor -- EBV-Derived Episomes to Probe Chromatin Structure and Gene Expression in Human Cells -- Triplex-Directed Site-Specific Genome Modification -- Use of Quantitative Ligation-Mediated Polymerase Chain Reaction to Detect Gene Targeting by Alkylating Oligodeoxynucleotides -- Gene Targeting in Plants via Site-Directed Mutagenesis -- Antisense Oligonucleotides as Modulators of Pre-mRNA Splicing.
Keywords: Human genetics; Human Genetics